Awareness and knowledge of various impression techniques for resorbed ridge in complete denture fabrication among dental students - Banu, Sarah; Duraisawamy, Revathy; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: Complete denture requires proper stability and retention for satisfactory results. In cases of resorbed ridges these two main properties are compromised. Complete denture fabrication of a resorbed mandibular ridge is more complicated when compared to that of maxilla. The need for recording the impression accurately is necessary for fabricating a good denture for resorbed ridges. Aim: The purpose of this survey was to determine the awareness of various impression techniques used for resorbed ridges for fabricating a complete denture among dental students in South Indian population. Materials and methods: A self-administrative questionnaire especially designed for this study, was distributed among 100 individuals. The questionnaire consisted of 10 questions. Results: The awareness on the various impression techniques used for resorbed ridge was very low (40%) among the dental students. The awareness of the different impression materials (20%) used for resorbed ridges was also not found to be satisfactory. A percentage of only 40 believed that it was possible to make a complete denture in highly resorbed ridge successfully. Conclusion: A very poor response was found in the awareness of various impression techniques in highly resorbed ridges among dental students. An awareness can be created by giving short classes on how to manage highly resorbed ridges to increase the knowledge of dental students and to increase their confidence on managing patients with highly resorbed ridges.